Exploring the Role of Human Resource Management in Advancing Change in the Public Sector - Akinseye Olowu (E-Journal of Humanities, Arts and Social Sciences)
The role of HRM in advancing change in the public sector has become a key influencer in shaping the trajectory of public service delivery across the globe. The role that HRM has had to play in the current international system cannot be downplayed. As a principal agent for service delivery of government functions, the process of human resource management in the public sector has a first-line impact on the performance of government functions and the realization of its programmes and policies. With the current trend across the globe towards a digital economy, human resource management of the public sector is still in the transition stage from traditional personnel management to modern human resource management in developing countries. The Principal Agent Theory serves as the theoretical framework for the analysis of this study. The underlying presumptions of this paradigm include the following: actors act in a way that maximizes benefits; there are conflicts of interest; actors’ rationality is limited; and there are information asymmetries between principals and agents. The actors are able to use the discretionary scope for actions that maximize their own gains thanks to these information asymmetries. Secondary sources of data were used to collect data. The study findings revealed that change management continues to be a primary concern for HR directors, particularly in light of the negative effects that too much change and uncertainty are having on public sector businesses. However, workers should be continuously trained to align with the constant change dynamic in the public sector.